Clarifications on the Taxation of Micro-enterprises’ Income in the Context of the Amendment to the Methodological Norms for the Application of the Fiscal Code - Lucian CERNUȘCA (CECCAR Business Review)

(untitled)
The Methodological Norms for the application of the Fiscal Code have recently been adjusted by Government Decision No. 1393/2024, in force since November 11, 2024, in order to clarify some issues that professional accountants face in their practical activity. Among these are clarifications related to the taxation of microenterprise income, which will be discussed in this article. The changes occurred in the norms for the application of the Fiscal Code come in the context of Law No. 296/2023 and Government Emergency Ordinance No. 115/2023. They define the concept of indirect holding in microenterprises and provide clarifications regarding the activity carried out as an authorized natural person/individual enterprise/family enterprise with regard to the verification of related enterprises for the application or nonapplication of microenterprise income tax. The norms also clarify the condition regarding the timely submission of annual financial statements and present a list of legal persons that are not subject to the microenterprise income tax system.